MIGRASI NELAYAN ASAL PASURUAN KE KOTA BALIKPAPAN (KASUS PADA KELOMPOK NELAYAN HARAPAN BARU) - Tri Sukma Putra; Qoriah Saleha; Erwan Sulistianto (Jurnal Pembangunan Perikanan dan Agribisnis, 2016)
The purpose of this research was to know the motivation of fishermen from Pasuruan village migrated to Manggar Baru. Village, Public Perception to fishery resources in Balikpapan city, the research method used Case Study. The analyzed data method used descriptive and quantitative analysis. The result of research was the motivation fisherman group of Harapan Baru. Migrate to Manggar Baru is to found new fisheries resources in Balikpapan City, they perception of the fish and shrimp stock at Balipapan sea is moderat.